2012
DOI: 10.1007/s10792-012-9595-4
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis application for myopia over minus 14 diopter with long-term follow-up

Abstract: The manifest average spherical equivalent refraction was -21.7 ± 5.8 D prior to surgery. This value became -6.0 ± 3.3 D after at least 10 years of follow-up. The regression was -6.1 ± 2.2 D in the period starting from the first month of the follow-up until the last control. The uncorrected visual acuity was 0.07 ± 0.1 at the last follow-up. The mean preoperative best-corrected visual acuity (BCVA) was 0.22 ± 0.12 and 0.30 ± 0.17 postoperatively (p < 0.001). Loss or gain of one line or more at the BCVA in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
0
11
0
6
Order By: Relevance
“…Rosman et al stated that mean regression at 10 years after LASIK was −1.86 D in eyes with myopia of −14.33 ± 2.11 D [17]. Oruçoğlu et al and Lim et al described that mean final refraction was −6.09 D and −1.09 D in eyes with myopia of −21.70 ± 5.86 D and −5.73 ± 2.76 D, respectively [18, 20]. In the current study, similarly, we found refractive regression of −0.74 ± 0.99 D from 3 months to 12 years postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Rosman et al stated that mean regression at 10 years after LASIK was −1.86 D in eyes with myopia of −14.33 ± 2.11 D [17]. Oruçoğlu et al and Lim et al described that mean final refraction was −6.09 D and −1.09 D in eyes with myopia of −21.70 ± 5.86 D and −5.73 ± 2.76 D, respectively [18, 20]. In the current study, similarly, we found refractive regression of −0.74 ± 0.99 D from 3 months to 12 years postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant average trend towards myopic regression of − 0.51 D between 1 and 24 months (P < 0.001), which is small considering this VHM group. Patients with high myopia are more likely to regress, with regression being reported to be more pronounced between 3 and 12 months [15,[33][34][35]. There may be less regression here than expected due to newer aspheric larger ablation profiles (Custom-Q®), improving stability.…”
Section: Complicationsmentioning
confidence: 99%
“… 3 Specifically, in correcting moderate to high myopia (equal or more than −6.00 D in the least-minus meridian), 4 , 5 there have been reports in the past indicating significant long-term regression. 6 8 The work by Alió et al 9 reported that 20.8% of high myopia cases required retreatment because of over- or undercorrection, or regression. Other studies have shown that the risk of regression may be between 5% and 27%.…”
Section: Introductionmentioning
confidence: 99%